2023
DOI: 10.3390/tomography9050126
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Quantitative Assessment of Arthroscopically Proven Long Biceps Tendon Pathologies Using T2 Mapping

Patrick Stein,
Felix Wuennemann,
Thomas Schneider
et al.

Abstract: This study evaluates how far T2 mapping can identify arthroscopically confirmed pathologies in the long biceps tendon (LBT) and quantify the T2 values in healthy and pathological tendon substance. This study comprised eighteen patients experiencing serious shoulder discomfort, all of whom underwent magnetic resonance imaging, including T2 mapping sequences, followed by shoulder joint arthroscopy. Regions of interest were meticulously positioned on their respective T2 maps, capturing the sulcal portion of the L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…T2 mapping has been studied for its capability to detect and quantify anomalies in the long biceps tendon (LBT) [16]. The research aimed to understand how effectively T2 mapping can identify arthroscopically confirmed LBT pathologies and measure T2 values in both healthy and damaged tendons.…”
Section: Applications Of Image Analysis In Musculoskeletal Imagingmentioning
confidence: 99%
“…T2 mapping has been studied for its capability to detect and quantify anomalies in the long biceps tendon (LBT) [16]. The research aimed to understand how effectively T2 mapping can identify arthroscopically confirmed LBT pathologies and measure T2 values in both healthy and damaged tendons.…”
Section: Applications Of Image Analysis In Musculoskeletal Imagingmentioning
confidence: 99%